2017
DOI: 10.1111/iej.12872
|View full text |Cite
|
Sign up to set email alerts
|

Human periodontal ligament fibroblasts synthesize C‐reactive protein and Th‐related cytokines in response to interleukin (IL)‐6 trans‐signalling

Abstract: IL-6 trans-signalling induced Th1 and Th17-related cytokines and represents an extra-hepatic mechanism for PCR synthesis in human periodontal ligament fibroblasts, contributing to explain the bone-destructive phenotype of apical lesions and eventually its systemic complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Inflammation is a complex cascade of events that may lead to its resolution or, alternatively, to its stalling into a chronic condition that renders the management of the clinical condition hard to accomplish. The molecular events involved in this scenario are: an exaggerated production of IL-6 [33] and the consequent activation of the transcription factor STAT3 [34] that primes the production and release of several additional cytokines that sustain and maintain the inflammatory state. Among those cytokines, IL-17A is of paramount importance in the context of oral disease.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation is a complex cascade of events that may lead to its resolution or, alternatively, to its stalling into a chronic condition that renders the management of the clinical condition hard to accomplish. The molecular events involved in this scenario are: an exaggerated production of IL-6 [33] and the consequent activation of the transcription factor STAT3 [34] that primes the production and release of several additional cytokines that sustain and maintain the inflammatory state. Among those cytokines, IL-17A is of paramount importance in the context of oral disease.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we found statistically higher CRP levels in GCF from individuals affected by both periodontitis and gingivitis, compared to healthy ones. Considering the lack of an evident association between periodontal disease and serum CRP levels found in our study, the aforementioned fact might be explained, to some extent, by a local production of CRP within periodontal tissues, which has been previously reported and demonstrated [19,40]. However, moderate to strong positive correlations between the concentrations of this protein in GCF and serum were also evidenced in all study groups, showing that CRP measurements in GCF may reflect its serum levels, as demonstrated in past works [18,25].…”
Section: Discussionmentioning
confidence: 49%
“…The pathological features of periapical periodontitis are inflammation of the apical area and destruction of bone tissue (Hernández et al, 2018, Kirkevang, Ørstavik, Bahrami, Wenzel, & Vaeth, 2017Wei, Liu, Xiong, Peng, 2018). This results in immune inflammatory responses, which involve a large number of inflammatory cells that are regulated by a variety of cytokines (Provenzano et al, 2016;Sasaki et al, 2016).…”
Section: Discussionmentioning
confidence: 99%